HTML in easy steps - McGrath, Mike, 1956- (In easy steps., 2020)
"[This book] has an easy-to-follow style that will appeal to anyone looking to create compelling web pages for the latest browsers. Ideal for programmers who need to quickly learn the latest HTML techniques, students learning website design at school or college, those seeking a career in web development who need a thorough understanding of HTML, and the enthusiast eager to build the latest HTML features into their websites." -- From Amazon.com summary.